2021
DOI: 10.1002/cctc.202101095
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Highly Selective Carbon‐Supported Boron for Oxidative Dehydrogenation of Propane (ChemCatChem 16/2021)

Abstract: The Cover Feature shows “The Catalyst Store” that contains a variety of catalysts used in important chemical transformations. In the foreground is the shelf housing oxidative dehydrogenation catalysts, featuring the exciting new boron‐based catalysts as well as traditional vanadium oxide‐based catalysts. Top‐shelf options are the highly‐selective h‐BN and the newly described B/C – an equally selective, higher performing, and less expensive ODH catalyst that h‐BN. In their Full Paper, L. O. Mark, R. W. Dorn et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…16 The pristine BN material was found to be readily oxidized and hydrolyzed under ODH reaction conditions, producing a phase consisting of triple-liganded boron sites with varying numbers of hydroxyl groups and bridging oxide groups (B 2 (OH) 2x O 3−x (x = 0-3)), significant for catalytic activity. 17,18 Lu et al marked the OH formed on the NB surface by isotope labeling, which proved that the B-OH formed on the NB edge was involved in the ODH reaction. 19 Venegas et al observed that the catalyst bed height could be adjusted by mixing SiC into h-BN, 20 suggesting that the catalytic activity may originate from the gas-phase oxidation chemistry triggered by catalytic surface reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The pristine BN material was found to be readily oxidized and hydrolyzed under ODH reaction conditions, producing a phase consisting of triple-liganded boron sites with varying numbers of hydroxyl groups and bridging oxide groups (B 2 (OH) 2x O 3−x (x = 0-3)), significant for catalytic activity. 17,18 Lu et al marked the OH formed on the NB surface by isotope labeling, which proved that the B-OH formed on the NB edge was involved in the ODH reaction. 19 Venegas et al observed that the catalyst bed height could be adjusted by mixing SiC into h-BN, 20 suggesting that the catalytic activity may originate from the gas-phase oxidation chemistry triggered by catalytic surface reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Supported boron oxide catalysts can provide abundant "BO" sites on the surface, and exhibit high activity in ODHP. 17,18,25 It has been reported that B 2 O 3 impregnation on conventional three-dimensional porous supports, 9,26,27 such as TiO 2 , SiO 2 and Al 2 O 3 , could enhance the abundance of "BO" sites on the catalyst surface for the oxidative dehydrogenation reaction. However, under the higher reaction temperature (mostly >450 °C) normally used for the oxidative dehydrogenation of propane, the above catalysts may suffer from insufficient stability due to the low melting point of boron oxide (∼450 °C), 12,22 easily causing its liquefaction on the catalyst surface, weakening the interaction force between boron oxide and the carrier and even leading to the loss of boron.…”
Section: Introductionmentioning
confidence: 99%